Partial resistance factors of class 4 steel elements - Giżejowski, Marian; Stachura, Zbigniew (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
Problems related to partial resistance factors of class 4 steel elements are dealt with. Detailed procedures for the calculation of local stability resistance reduction factors are presented. Local instability approaches are utilized for the resistance assessment of elements subjected to buckling in compression and lateral buckling in bending.